2024
DOI: 10.3390/buildings14010281
|View full text |Cite
|
Sign up to set email alerts
|

Circular Material Usage Strategies and Principles in Buildings: A Review

Paulo Santos,
Génesis Camila Cervantes,
Alicia Zaragoza-Benzal
et al.

Abstract: Building construction accounts for a significant proportion of global greenhouse gas emissions, raw material extraction, and waste production. Applying circular economy (CE) principles in the building construction industry would considerably reduce these values. However, uptake by the industry is relatively slow, which is largely attributed to sectoral barriers, including limitations in knowledge and experience. This review paper aims to assess and contribute to diminishing these obstacles by offering a compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 125 publications
(200 reference statements)
0
0
0
Order By: Relevance
“…Fagone, C. et al, 2023 [64] created a flow of site operations on circularity based approaches. Santos, P. et al, 2024 [65] identified patterns, relationships, etc by giving further valuable insights. Tsui, Tanya, 2022 [66] discussed municipal-led circular land mass coordination.…”
Section: Theoretical Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fagone, C. et al, 2023 [64] created a flow of site operations on circularity based approaches. Santos, P. et al, 2024 [65] identified patterns, relationships, etc by giving further valuable insights. Tsui, Tanya, 2022 [66] discussed municipal-led circular land mass coordination.…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Noorshella Che Nawi et al, 2024 [89] researched on electronic wallet adoption whereas Lyngby (2008) [89] was suggesting coordinated purchasing as an effective measure to support circularity. Santos, P.; et al, 2024 [92] researched on novel block system, recycled aggregate, modular kitchen reuse, and energy efficiency retrofit whereas Melella, R et al, 2021 [93] investigated on selective, low carbon disassembly and demolition. Meng, X et al, 2023 [94] empirically investigated on the integration of digital twin.…”
Section: Practical Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fagone, C. et al, 2023 [72] created a flow of site operations on circularity based approaches. Santos, P. et al, 2024 [73] identified patterns, relationships, etc by giving further valuable insights. Tsui, Tanya, 2022 [74] discussed municipal-led circular land mass coordination whereas Paulo de Sa & Jane Korinek, 2021 [75] contributed in offering savings to offset green premium for mass consumers.…”
Section: Literature Surveymentioning
confidence: 99%